ANTHROPONYMS AS AN OBJECT OF LINGUOCULTUROLOGICAL RESEARCH (TAMADDUN NURI JURNALI, 2024)
In this article the discussed question is the present day status of the language, as well as the role of deep  onomastic research into its folk art on the way of development, specitically, there is discussion about human names used in karakalpak  folklore, which made a huge impact on centuries old traditions of name giving among karakalpak people.